Methods of teaching preferred by students learning Islamic education: A case study at Jamiyah Education Centre, Singapore - Rustham, Nora; Mamat , Arifin; Abd Rashid, Adnan (2013)
Jamiyah Education Centre is a non-profit organization that aims to provide service to humanity by promoting missionary, education and welfare The centre provides Islamic education to all Muslims in Singapore ranging from preschoolers to adults. This study examines the teaching methods that are mostly used by the Islamic education teachers at JEC and the most preferred methods from the students’ perspectives. The survey method was employed in this study. The sample consists of three hundreds and two (302) students. The study used a set of questionnaire for students to gather the data. Meanwhile the descriptive statistics were used for the data analysis. This study revealed that the teaching methods that are frequently employed by the JEC teachers is the method of lecture. The findings also indicated that the most preferred teaching methods by the students is the use of humor.